THE DETERMINATION OF THE STATISTICAL PARAMETERS OF THE CONVERTERS IN CIRCUITS TEST STANDS FOR TRACTION MOTORS OF THE LOCOMOTIVE - Bezruchenko, V. M.; Marenych, O. L. (Science and Transport Progress, 2009)
In the article the method of static converters parameters calculation is resulted. It is proposed to replace the electromachine linear generator and balancing booster with static converters in the scheme of the traditional stand for test of locomotives traction engines.